Design of the emergency power of National Archive Building Musheireb Downtown Doha, Qatar - Manuel, Clemente R. (Manila Professional Regulation Commission, 2014)
The National Archive Building at Musheireb Downtown Doha, Qatar is a Government building which will be used as storehouse of the nation's heritage and is based on the form of the traditional fortified tower. The building project involves construction of a museum comprising 2 basement levels, a ground floor and 12 additional floors mostly library with a total floor area of 26,073 square meters Emergency Power of the National Archive Building will be supplied by 3 sets of 2000 kVA, 415 V, 3 phase Cummins Generators such as Generator 1, Generator 2 and Generator 3. Each Standby Diesel Generator has individual distribution switchgear respectively connected to each group of ATS with different preset response setting to minimize starting kVA that could be contributed by all inductive loads. The purpose of this report is to present the recalculation of Emergency Power Distribution System of Generator 1 of National Archive Building which was originally designed by Burns & McDonnell Incorporated, Kansas City, USA is being managed and was developed by Government Agency Musheireb Property, Doha, State of Qatar. The author was assigned as an Electrical Engineer and became a part of the supervision team in different construction buildings along Phase 1 of which National Archive building is one of those. This technical report shall involve substantial calculation such as load calculation and each layout plan with respect to load schedule, generating set size determination, wires and cables sizing, circuit breaker rating short circuit calculation, and protective devices. The related references books which were utilized articles in this technical report were based on applicable codes, regulation and standard used loca lly in the State of Qatar and International. So carefully recommended as part of conclusion in this report were in should be enumerated to impart observation and evaluation as a result of the real technical reason of this report.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-671G donated by Mr. Jaime E. Mendoza.
Keywords: Buildings -- Electric equipment